Autism and Down syndrome: early identification and diagnosis - Diniz, Natália Lisce Fioravante; Parlato-Oliveira, Erika; Pimenta, Priscila Gonçalves Ayres; Araújo, Liubiana Arantes de; Valadares, Eugênia Ribeiro (Arquivos de Neuro-Psiquiatria, 2022)
Background: The diagnosis of autism spectrum disorder (ASD) in Down syndrome (DS) is underestimated because it is necessary to understand which aspects of the behavioral phenotype are related to DS and which are related to ASD. Objective: To conduct a systematic review of the literature on early identification and diagnosis of ASD in patients with DS. Data source: The VHL, MEDLINE, Cochrane, CINAHL, Scopus, Web of Science and Embase databases were searched and data were evaluated using PRISMA. Data synthesis: Out of 1,729 articles evaluated, 15 were selected. Although well studied, identification of ASD in DS can be difficult because of the need to understand which aspects of the behavioral phenotype are related to Down syndrome and which to autism. In this review, the prevalence of ASD was found to range from 12% to 41%. Early identification of autism risk in individuals with Down syndrome is still poorly studied, even though there are screening instruments for infants. Several instruments for diagnosing autism in individuals with Down syndrome were found, but a developmental approach is fundamental for making a clear diagnosis. Conclusions: Screening procedures are important for detecting early signs of autism risk in the first year of life. Careful evaluation methods are needed to establish the diagnosis, which include choosing appropriate tools for evaluation of development and cognition, and analysis of qualitative aspects of social interaction, among others. It has been indicated in the literature that early detection and timely accurate diagnosis, in association with an intervention, may benefit development, quality of life and social inclusion.
Keywords: Autism Spectrum Disorder; Down Syndrome; Diagnosis